Drugs that lower the seizure threshold. (June 2016) - Hitchings, Andrew W.
Abstract : Summary: Drugs with potential to lower the seizure threshold are numerous and diverse. Whether they contribute to clinically overt seizures depends on the dosage in which they are taken, the time-course of their effects and the susceptibility of the patient. Crucially, however, their contribution to seizure risk is potentially modifiable.